Fatty Acid Biohydrogenation, Fermentation, and Digestibility of Ration Containing Napier and King Grass with Different Harvest Ages and Altitudes: In Vitro Study - Anzhany, D.; Toharmat, T.; Despal; Łozicki , A. (Faculty of Animal Science, IPB University, 2024)
Forage is the primary and cheapest source of fatty acids (FA), which includes conjugated linoleic acid (CLA), influencing milk FA. This study aimed to analyze the fermentation, digestibility, biohydrogenation, nutrient composition, and FA content of napier grass (NG) and king grass (KG). Grasses were collected from the Pangalengan (highland) and Dramaga (lowland) districts at three harvest ages (1, 1.5, and 2 months). The feed was then analyzed for nutrients and FA. An in vitro study was performed to analyze the concentrations of NH3, VFA, protozoa populations, and biohydrogenation. No significant differences were observed in protozoa, pH, total VFA, or FA biohydrogenation. NH3 ranged from 5.31 mM to 8.86 mM. Significant differences were found at different altitudes, with an interaction between grass type and harvest age and an interaction between the three factors. The highest NH3 concentration was found in rations containing highland NG at 1.5 months. The DMD value was 58.27%–64.39%, and OMD was 61.07%–67.18%. Different digestibility values were observed at different harvest ages, with an interaction between altitude and harvest age. This aligned with the CF, NDF, and lignin contents in grasses. The highest was at 1.5 months NG. Significant differences were observed in the relative proportions of propionic acids. The highest value was in the ration containing the 1.5-month highland NG. Rations containing KG yielded significantly higher amounts of the C18:0 and C18:1 trans. In conclusion, the 1.5-month highland NG is a potential ration for supporting healthier FA production in milk.